Analysis of Implementation of Government Fiscal Policy to Overcome Poverty in East Java - Fauzi, Moh. Rifqi (CV. Civiliza Publishing, 2023)
Introduction/Main Objectives: This research aims to analyze how the Government's Fiscal Policy is Implemented to Overcome the East Java Poverty Problem for the 2020-2021 period. Research Methods: The research method used is a qualitative method with a descriptive research methodology approach with content analysis and library research techniques. Research that utilizes library resources to obtain research data. Finding/Results: The results of the study show that the efforts made by the Provincial Government of East Java to overcome poverty are through various comprehensive poverty reduction programs, including social assistance for individuals and families, community empowerment and MSME empowerment, and other poverty reduction programs. Conclusion: With the right fiscal Policy, the government can overcome the problem of poverty. Then fiscal Policy is beneficial to improve people's welfare.